Analyzing the Impact of Political Stability on FDI Inflows in SAARC Nations : A Panel ARDL Cointegration Approach - Kaur, Muskan; Vij, Madhu (Indian Journal of Finance, 2020)
The present research work analyzed the influence of political stability on foreign direct investments (FDI) for the South Asian Association for Regional Cooperation (SAARC) nations. The study analyzed a panel of four countries, namely India, Bangladesh, Pakistan, and Sri Lanka. The time frame considered for analysis was from 2000 – 2017. The panel auto-regressive distributive lag (ARDL) cointegration methodology was applied to assess FDI inflows’ impact on political stability of select SAARC nations. The results of panel ARDL exhibited significant and positive influence of political stability on FDI inflows in the long and short run. Long run causality and joint causality were also established amongst the political stability components and FDI inflows. The study advised SAARC nations to consider desired actions for improving the investment scenario and keep political situation stable in the region. The government, leaders, and policy makers are also advised to pay due consideration to the political stability to keep low investor scepticism and attract more FDIs in the economy.